The U.S. South and Europe : Transatlantic Relations in the Nineteenth and Twentieth Centuries. - Minnen, Cornelis A. van (New directions in southern history., 2013)
The U.S. South is a distinctive political and cultural force -- not only in the eyes of Americans, but also in the estimation of many Europeans. The region played a distinctive role as a major agricultural center and the source of much of the wealth in early America, but it has also served as a catalyst for the nation's only civil war, and later, as a battleground in violent civil rights conflicts. Once considered isolated and benighted by the international community, the South has recently evoked considerable interest among popular audiences and academic observers on both sides of the Atla.